2018
DOI: 10.1007/s00262-018-2123-2
|View full text |Cite
|
Sign up to set email alerts
|

Identification of tumor-reactive B cells and systemic IgG in breast cancer based on clonal frequency in the sentinel lymph node

Abstract: A better understanding of antitumor immune responses is the key to advancing the field of cancer immunotherapy. Endogenous immunity in cancer patients, such as circulating anticancer antibodies or tumor-reactive B cells, has been historically yet incompletely described. Here, we demonstrate that tumor-draining (sentinel) lymph node (SN) is a rich source for tumor-reactive B cells that give rise to systemic IgG anticancer antibodies circulating in the bloodstream of breast cancer patients. Using a synergistic c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 43 publications
(49 reference statements)
2
18
0
Order By: Relevance
“…The opposite was also true, the presence of given autoantibodies in the circulation was not indicative of the autoantibody production in situ . Whether such B cells were activated in draining lymph nodes as it has been recently demonstrated for anti-CTAG1B B cells in BC patients ( 39 ) and never infiltrated the tumors or whether they were activated in BC-associated TLS but left the tissue is not known.…”
Section: Discussionmentioning
confidence: 95%
“…The opposite was also true, the presence of given autoantibodies in the circulation was not indicative of the autoantibody production in situ . Whether such B cells were activated in draining lymph nodes as it has been recently demonstrated for anti-CTAG1B B cells in BC patients ( 39 ) and never infiltrated the tumors or whether they were activated in BC-associated TLS but left the tissue is not known.…”
Section: Discussionmentioning
confidence: 95%
“…Studies have shown that antigen-driven B cells migrate into the breast tumor microenvironment, proliferate, undergo somatic hypermutation and affinity maturation. 22 – 24 However, it is unclear as to the extent of this B cell activity in patients that have recurrences, distant metastasis, or poor disease-free and overall survival. Therefore, follow-up studies to test the function of B cells from breast cancer patients are required for better characterization of B cells in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…A trend toward improved 5-year survival was noted in melanoma patients, whose SLNs demonstrated follicular hyperplasia/GC accumulation ( 88 ). Besides their prognostic value for disease-free survival in breast cancer patients ( 89 ), SLN B cells is the source of affinity matured B cell clones that produced anti-tumor immunoglobulins detected in the blood ( 90 ). Investigation of such antibodies could potentially lead to the recognition of tumor antigens recognized by the immune system, which can subsequently be targeted in the context of immunotherapies ( 90 ).…”
Section: Lymph Nodes In Neoplasmsmentioning
confidence: 99%
“…Besides their prognostic value for disease-free survival in breast cancer patients ( 89 ), SLN B cells is the source of affinity matured B cell clones that produced anti-tumor immunoglobulins detected in the blood ( 90 ). Investigation of such antibodies could potentially lead to the recognition of tumor antigens recognized by the immune system, which can subsequently be targeted in the context of immunotherapies ( 90 ). Furthermore, these findings imply that development of tumor-specific Tfh cells could be a critical factor for an effector response to a tumor.…”
Section: Lymph Nodes In Neoplasmsmentioning
confidence: 99%